Hepatitis A virus – a general overview - Yong, Han Tek; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Hepatitis A virus infection occurs globally and is causing a public health concern, primarily in developing countries due to its persistent circulation in the environment. The improved sanitary condition and increase in awareness of personal hygiene have led to the marked reduction of HAV prevalence in industrialized countries during childhood and to a shift of the infection towards adulthood. HAV is an environmentally stable, positive single stranded RNA virus that is primarily transmitted by the fecal-oral route, person to person contact or ingestion of contaminated food and drink. One of the main causes leading to HAV infection is epidemiologically linked to the consumption of raw or undercooked shellfish particularly oysters and clams. Due to their filter-feeding style, these shellfishes readily concentrate viruses from the surrounding water containing municipal sewage, and as a consequence pose a health threat to consumers. Therefore, development of detection techniques possessing the requisite sensitivity and specificity for the practical routine monitoring purposes is of great importance necessary for the protection of shellfish-consuming public. Nucleic acid based method such as reverse transcription PCR has emerged as the popular method of choice in view of its rapidity, accuracy and sensitivity in contrary of the time-consuming conventional cell culture and hybridization techniques. However, detection of hepatitis A virus is firstly hampered by the non-cytophatic effect of wild type HAV strain, secondly, the low concentration of viral genome present in the environmental sample which requires effective isolation and concentration of virions and lastly the labor-extensive purification and thorough removal of the abundance of the PCR inhibitors which will unfavorably reduce the efficiency of PCR detection.